The Utilization of Standard Costs in Performance-Based Budgeting System in Indonesian Government Institutions - Afiah, Nunuy Nur; Alfian, Adhi; Hasan, Annisa Nabila (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2025)
Research Originalty — The Indonesian government has implemented performance-based budgeting (PBB) for more than 20 years since 2003. The main goal is to increase accountability of financial management. Standard cost is one of the three basic instruments of PBB. However, there are several issues in standard cost utilization both in central and local governments. Research Objectives — This research was conducted to provide an overview of the implementation process of the standard costs in Indonesia and to propose future improvements. Research Methods — We used a content analysis approach as the main instrument to provide inter-correlated information on various materials used as research data. The data analysis was deductive with developed analysis structure based on previous knowledge. Empirical Results — The results showed that although output-based standards were the most appropriate tool for the PBB, input-based cost standards were predominantly used. Various efforts need to be made to improve the suitability of standard costs to ensure they remain relevant and aligned with market prices. Implications — Several other factors are also important to apply standard costs. These are regulatory consistency, stakeholder understanding of the standard components use, and the use of information system solutions to facilitate integration of the budgeting process.